2003
DOI: 10.1046/j.1442-2042.2003.00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor gene polymorphism in familial prostate cancer in a Japanese population

Abstract: Aim

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 20 publications
(23 reference statements)
4
30
0
Order By: Relevance
“…Genotype frequencies were also similar in women with breast cancer and in the control population. Our data are consistent with reports on breast (Schndorf et al, 2003) and prostate cancer (Ma et al, 1998;Suzuki et al, 2003).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Genotype frequencies were also similar in women with breast cancer and in the control population. Our data are consistent with reports on breast (Schndorf et al, 2003) and prostate cancer (Ma et al, 1998;Suzuki et al, 2003).…”
Section: Discussionsupporting
confidence: 83%
“…Genotype frequencies were also similar in women with breast cancer and in the control population. Our data are consistent with reports on breast (Schndorf et al, 2003) and prostate cancer (Ma et al, 1998;Suzuki et al, 2003).It has been reported that individuals homozygous for the t allele are significantly underrepresented among prostate cancer patients, illustrating a protective role for the t allele in prostate carcinogenesis (Taylor et al, 1996; Hamasaki et al, 1999). However, these findings have not been corroborated in later studies (Blazer et al, 2000;Habuchi et al, 2000).…”
supporting
confidence: 83%
“…Among Japanese populations, ApaI was not statistically significantly associated with either familial prostate cancer (30) or sporadic prostate cancer and benign prostatic hyperplasia (13). The TaqI tt genotype has been inversely associated with prostate cancer (25), although most studies did not detect any such a results (12,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…In which the objects were Asian population in 12 articles; and one was not control study (Bid et al, 2005); two shared the prostate cancer cases (Jianhe et al, 2004a;Jianhe et al, 2004b), so we only chose one according to our exclusion criteria (Jianhe et al, 2004a). At last, 10 articles were included in Meta-analysis (Watanabe et al, 1999;Habuchi et al, 2000;Hamasaki et al, 2001;Hamasaki et al, 2002;Suzuki et al, 2003;Huang et al, 2004;Jianhe et al, 2004a;Chaimuangraj et al, 2006;Onsory et al, 2008;Bai et al, 2009), including 1141 cases and 1685 control. The basic information are shown in Table 1.…”
Section: Basic Informationmentioning
confidence: 99%